Numerical and Experimental Analysis of Torsion Springs Using NURBS Curves - Young Shin Kim (Applied Sciences, 2020)
Torsion springs, which transfer power through the twisting of their coil, provide advantages such as module simplification and efficient use of space. The design of a torsion spring has been formulated, but it is difficult to determine the local behaviors of torsion springs according to actual load conditions. This study proposes a torsion-spring design method through finite element analysis (FEA) using nonuniform-rational-basis-spline (NURBS) curves. Through experimentation, the angle and displacement values for the actual spring load were converted into useable data. Torsion-spring displacement values were obtained via experimentation and converted into coordinates that may be expressed using NURBS curves. The results of these experiments were then compared to those obtained via FEA, and the validity of this method was thereby verified.